2014
DOI: 10.1002/mats.201400037
|View full text |Cite
|
Sign up to set email alerts
|

Design of Copolymers Based on Sequence Distribution for a Targeted Molecular Weight and Conversion

Abstract: It is challenging to track explicit copolymer sequences and related measures using continuum kinetic models. We developed a generalized framework based on kinetic Monte Carlo (KMC) to model free radical polymerization of any number of monomers to obtain the explicit sequence and its distribution. The KMC framework was applied to copolymerization of butyl acrylate/methyl methacrylate (BA/MMA) and methyl acrylate/methyl methacrylate (MA/MMA), and the simulation output was compared with experimental results. Sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 57 publications
(73 reference statements)
0
29
0
Order By: Relevance
“…The kinetic parameters for this system are available in the literature, [36][37][38][39][40] and previous studies have shown that it is sufficient to use constant apparent propagation and termination rate coefficients in this system. 15,41 This is taken into account in this model by assigning a large value to the monomer diffusion coefficient, so that the chemistry-controlled contribution to the rate coefficients always dominates over the diffusioncontrolled contribution. Physical properties and kinetic parameters are listed in Table 3.…”
Section: Butyl Acrylate (Ba)/methyl Methacrylate (Mma) Copolymerizationmentioning
confidence: 99%
See 3 more Smart Citations
“…The kinetic parameters for this system are available in the literature, [36][37][38][39][40] and previous studies have shown that it is sufficient to use constant apparent propagation and termination rate coefficients in this system. 15,41 This is taken into account in this model by assigning a large value to the monomer diffusion coefficient, so that the chemistry-controlled contribution to the rate coefficients always dominates over the diffusioncontrolled contribution. Physical properties and kinetic parameters are listed in Table 3.…”
Section: Butyl Acrylate (Ba)/methyl Methacrylate (Mma) Copolymerizationmentioning
confidence: 99%
“…One area where there has been growing interest in KMC is polymerization . The attractiveness of KMC is mainly because of two reasons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10,11] At the other extreme, Monte Carlo type probabilistic methods, more specifically kinetic Monte Carlo (kMC) developed by Gillespie, [12] attempt to obtain a solution for the entire distribution by simulating the behavior of a finite ensemble selected to approximate the actual physical system. [13][14][15] For example, the polymerization medium might be approximated by a collection of initiator molecules, and a collection of monomer molecules. Each species can undergo a specific set of chemical reactions at a probability proportional to the rate of each reaction.…”
Section: Introductionmentioning
confidence: 99%